Women's Social Capital for Empowering Poor Households - Willya Achmad; Nunung Nurwati; Muhammad Fedryansyah; R Widya Setiabudi Sumadinata (Universitas Dharma Wacana, 2022)
Adaptations were necessary as a result of the new family structure, which saw the mother taking on the role of primary breadwinner in addition to her other responsibilities. This was especially the case in order to ensure that the family continued to be financially successful. Maintaining and even improving the family economy is possible thanks to the ability of women to make use of economic resources by utilizing their social capital stock in the form of social networks that exist within the social environment. As a result, the purpose of this study is to investigate the function that women's capital plays in enhancing the economic standing of low-income families. In this investigation, a qualitative strategy is combined with a descriptive research approach. The findings demonstrated that women were able to raise the economic status of low-income families by utilizing their social capital stock in the form of social networks in the social environment. This was accomplished through the application of the concept of economic assistance to empower women through the operation of small and micro businesses. It will be easier to gain access to financial resources if one makes use of social networks and maintains positive relations with kin, among other social connections.